MULTITASKING ELEMEN BANGUNAN - Liauw, Franky (Universitas Tarumanagara, 2019)
Elements of architectural works in the form of buildings are usually described according to their respective roles. The dictionary is often a reference to understanding the meaning of each word, but it needs to be aware because the dictionary only gives a basic understanding, and often also becomes a barrier of thought that sometimes hinders further development. For example, in the dictionary the roof is defined as the top of the building cover, even though it has long been used as a roof garden. In the midst of many problems in the environment, such as the energy crisis, lack of non-renewable resources, global warming, various types of pollution, etc., empowering building elements for other functions outside their basic role, will provide added value, save costs and space, and various other benefits. This paper uses descriptive qualitative methods, in the form of a comparison of definitions in the dictionary with developments in architectural practice, as well as an analysis of the various possibilities and opportunities for the development of the role of each building element. The benefits of empowering building elements like this can be said to be environmentally friendly designs because they are in accordance with the principles of sustainable development. For example, the roof provides protection for the contents of buildings against uncomfortable external influences, but exposure to the sun with excessive heat can be converted to energy. The roof of the building can also accommodate human activities. Sports activities that release a lot of energy, can actually be converted into electrical energy through the empowerment of various building elements. Efforts to add as many other functions as possible to each building element in the architectural design process might be best taught from the beginning in architecture education courses so that it will become a habit inherent in every designer. Definitions in a dictionary need to be viewed more critically, not directly made as a rigid reference. AbstrakElemen karya arsitektur berupa bangunan biasanya diuraikan menurut peran masing-masing. Kamus sering menjadi acuan untuk memahami pengertian setiap kata, namun perlu diwaspadai karena kamus hanya memberi pengertian dasar, dan sering juga menjadi pembatas pemikiran yang kadang menghambat pengembangan lebih jauh. Sebagai contoh, dalam kamus atap didefinisikan sebagai penutup bangunan bagian atas, padahal sudah sejak lama atap digunakan juga sebagai roof garden. Di tengah banyaknya masalah dalam lingkungan, seperti krisis energi, kekurangan sumber daya tak terbarukan, pemanasan global, berbagai jenis polusi, dan lainnya, pemberdayaan elemen-elemen bangunan untuk fungsi-fungsi lain di luar peran dasarnya, akan memberi nilai tambah, menghemat biaya dan luasan ruang, dan berbagai manfaat lainnya. Tulisan ini menggunakan metode kualitatif deskriptif, berupa perbandingan definisi dalam kamus dengan perkembangan dalam praktek arsitektur, serta analisis berbagai kemungkinan dan peluang pengembangan peran setiap eleman bangunan. Manfaat pemberdayaan elemen bangunan seperti ini dapat dikatakan sebagai rancangan yang ramah lingkungan karena sesuai dengan prinsip pengembangan berkelanjutan. Sebagai contoh, atap memberi perlindungan bagi isi bangunan terhadap pengaruh luar yang tidak nyaman, namun paparan matahari dengan panas yang berlebihan dapat dikonversi menjadi energi. Atap bangunan juga dapat menampung kegiatan manusia. Kegiatan berolahraga yagn banyak mengeluarkan energi, sebenarnya dapat dikonversikan menjadi energi listrik melalui pemberdayaan berbagai elemen bangunan. Upaya menambahkan sebanyak mungkin fungsi lain pada setiap elemen bangunan dalam proses perancangan arsitektur mungkin sebaiknya diajarkan sejak awal di perkuliahan pendidikan arsitektur sehingga akan menjadi kebiasaan yang melekat pada setiap perancang. Definisi dalam kamus perlu dilihat dengan lebih kritis, tidak langsung dijadikan sebagai acuan yang kaku.